2021
DOI: 10.1186/s12883-021-02097-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistent inflammation worsens short-term outcomes in massive stroke patients

Abstract: Background Persistent inflammation is an important driver of disease progression and affects prognosis. Some indicators of inflammation predict short-term outcomes. The relationship between prognosis, especially mortality, and persistent inflammation in massive stroke has not been studied, and this has been the subject of our research. Methods From April 1, 2017 to February 1, 2020, consecutive patients were prospectively enrolled. Clinical data, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
(46 reference statements)
2
19
0
Order By: Relevance
“…Consecutive patients with either ischemic or hemorrhagic stroke were screened and selected from the Stroke Unit of Shanghai Fifth People’s Hospital between April 1, 2017, and February 1, 2020. The inclusion and exclusion criteria were the same as those reported in a previous study (see Supplemental materials ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consecutive patients with either ischemic or hemorrhagic stroke were screened and selected from the Stroke Unit of Shanghai Fifth People’s Hospital between April 1, 2017, and February 1, 2020. The inclusion and exclusion criteria were the same as those reported in a previous study (see Supplemental materials ) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is likely that this secondary peak in neuroinflammation is exacerbated by the concept of ‘inflammaging’. The term inflammaging alludes to the long-term condition of low-grade stimulation of the immune system, which essentially primes organisms to be more susceptible to inflammatory changes, such as those seen following stroke [ 175 , 176 ]. Suggesting that this secondary peak in neuroinflammation that is seen months after the initial insult may be exacerbated by a heightened inflammatory environment seen with ageing.…”
Section: Chronic Neuroinflammation In Strokementioning
confidence: 99%
“…This systematic review included 25 studies, of which 12 were retrospective [ 10 , 12 , 14 , 18 , 22 25 , 28 , 30 32 ] and 13 were prospective [ 4 , 9 , 11 , 13 , 15 17 , 19 21 , 26 , 27 , 29 ]. Among 25 studies, 15 were included in the meta-analysis; nine were retrospective [ 10 , 14 , 22 , 24 , 25 , 28 , 30 32 ], and six were prospective [ 11 , 13 , 20 , 26 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some studies were included solely in the qualitative review [ 4 , 9 , 12 , 15 19 , 21 , 23 ]. The majority of them assessed the relationship between NLR and PSP [ 4 , 9 , 12 , 15 18 , 21 , 23 ] and reported that NLR could predict pneumonia after stroke, similar to our findings. UTI is another type of PSP whose relationship with NLR was investigated in included studies.…”
Section: Discussionmentioning
confidence: 99%